2021
DOI: 10.3389/fpsyt.2021.651115
|View full text |Cite
|
Sign up to set email alerts
|

Using Imagery Rescripting as an Early Intervention for Depression in Young People

Abstract: Innovation is urgently needed for school-based early interventions for depression. Imagery rescripting for aversive memories has been shown to be a valuable therapeutic approach in adults. Yet it is rarely applied to young people or to depression. This is surprising given that intrusive images of aversive memories are implicated in the development and maintenance of depression. We review the literature and describe the co-development of an imagery rescripting protocol for young people (age 16–18) with high sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Setting for the study (3) begin as their current self and progress through a series of smaller images to their future self. For further details, see [24][25][26]. All imagery exercises are completed in the first person, present tense, and (when happy to) participants are asked to close their eyes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Setting for the study (3) begin as their current self and progress through a series of smaller images to their future self. For further details, see [24][25][26]. All imagery exercises are completed in the first person, present tense, and (when happy to) participants are asked to close their eyes.…”
Section: Methodsmentioning
confidence: 99%
“…Generating a positive future image similarly involved three steps: (1) imagining a vivid future image; (2) imagining they have achieved this future goal (future me) and speak to their current self (current me) to offer advice, speak about what has been positive and what has been difficult, and what has helped them achieve their goal; (3) begin as their current self and progress through a series of smaller images to their future self. For further details, see [ 24 26 ]. All imagery exercises are completed in the first person, present tense, and (when happy to) participants are asked to close their eyes.…”
Section: Methodsmentioning
confidence: 99%
“…A small number of studies have demonstrated that co-production can be used for school-based mental health interventions. For example, a targeted intervention for depression had extensive input from young people with experience of the disorder, parents, teachers and clinicians (Pile et al, 2021). This included an initial workshop about the overall approach of the study and detailed discussions about the intervention's content and delivery (the intervention involved one-to-one therapy using a technique called 'imagery rescripting' , in which people are taught to recall negative memories in a more helpful way).…”
Section: Involve Young People At All Stages Of Intervention Design An...mentioning
confidence: 99%